Glass ceiling for women and work attachment: the moderating effect of marital status (Case study: female employees of health centers in the east of Gilan province) - Khoshbahari, Roghayeh; Hosseinipour, Vahid; Pourkazemi, Vahab (Open Science Journal, 2022)
This study aimed to investigate the relationship between glass ceiling for women and work attachment due to the moderating effect of marital status among female employees of health centers in the east of Gilan province. In this study, glass ceiling for women, work attachment, and marital status were considered as an independent variable, a dependent variable and a moderating variable, respectively. The method of the present study is descriptive survey and the statistical population of the present study is the female employees of the executive and government agencies in the east of Gilan province, which will be a statistical sample among the people present in this community. In order to analyze the statistical data and test the research hypotheses using SPSS24 and SmartPLS3 statistical software, structural equation modeling has been performed. The results indicated that the glass ceiling for women has a significant effect on women's work attachment in health centers in the east of Gilan. However, marital status does not have a moderating effect on the relationship between the glass ceiling for women and women's work attachment in the east of Gilan health centers.